Empowering Social Support Networks for Returned Migrant Workers in Dalegan Village, East Java Indonesia - Rifat Nurwita Kusumaningtyas; Izzatul Fithriyah; Rina Kusumaratna (Universitas Malahayati Lampung, 2026)
ABSTRACT Returned migrant workers often face psychosocial challenges during reintegration, particularly in rural coastal areas with limited access to mental health services. This community service program in Dalegan Village, East Java, aimed to identify psychosocial needs and provide one-on-one counseling while strengthening social support networks through cadre involvement, family engagement, and NGO collaboration. A cross-sectional assessment was conducted with 24 participants using demographic questionnaires, DASS-21, and MSPSS, followed by individualized counseling. Results showed most participants had normal psychological status (83%), while a minority experienced stress, depression, or anxiety. Perceived social support was moderate to high (96%), especially among married participants, those with higher education, and nuclear families. Community discussions emphasized cadre mobilization and family-based support. This PKM activity demonstrates that integrating psychosocial assessment and counseling into village-level reintegration programs strengthens support networks and enhances resilience, ensuring reintegration is socially protective and sustainable. Keywords: Community Psychiatry, Counseling, Psychosocial Support, Returned Migrant Workers, Village Empowerment.